A survey of paediatric HIV programmatic and clinical management practices in Asia and sub-Saharan Africa - The International epidemiologic Databases to Evaluate AIDS (IeDEA) - V. Saphonn (2018)
Introduction: There are limited data on paediatric HIV care and treatment programmes in low-resource settings. Methods: A standardized survey was completed by International epidemiologic Databases to Evaluate AIDS paediatric cohort sites in the regions of Asia-Pacific (AP), Central Africa (CA), East Africa (EA), Southern Africa (SA) and West Africa (WA) to understand operational resource availability and paediatric management practices. Data were collected through January 2010 using a secure, web-based software program (REDCap). Results: A total of 64,552 children were under care at 63 clinics (AP, N =10; CA, N =4; EA, N =29; SA, N =10; WA, N =10). Most were in urban settings (N =41, 65%) and received funding from governments (N =51, 81%), PEPFAR (N =34, 54%), and/or the Global Fund (N =15, 24%). The majority were combined adult-paediatric clinics (N =36, 57%). Prevention of mother-to-child transmission was integrated at 35 (56%) sites; 89% (N =56) had access to DNA PCR for infant diagnosis. African (N =40/53) but not Asian sites recommended exclusive breastfeeding up until 4-6 months. Regular laboratory monitoring included CD4 (N =60, 95%), and viral load (N =24, 38%). Although 42 (67%) sites had the ability to conduct acid-fast bacilli (AFB) smears, 23 (37%) sites could conduct AFB cultures and 18 (29%) sites could conduct tuberculosis drug susceptibility testing. Loss to follow-up was defined as >3 months of lost contact for 25 (40%) sites, >6 months for 27 sites (43%) and >12 months for 6 sites (10%). Telephone calls (N =52, 83%) and outreach worker home visits to trace children lost to follow-up (N =45, 71%) were common. Conclusions: In general, there was a high level of patient and laboratory monitoring within this multiregional paediatric cohort consortium that will facilitate detailed observational research studies. Practices will continue to be monitored as the WHO/UNAIDS Treatment 2.0 framework is implemented. © 2013 IeDEA Pediatric Working Group; licensee International AIDS Society.